Managing PBL difficulties in an industrial engineering and management program - Alves, Anabela Carvalho (2016)
Purpose: Project-Based Learning (PBL) is considered to be an active learning methodology which can be used to develop both technical and transversal competences in engineering programs. This methodology demands a great deal of work effort from the students and also from the teachers and it requires a meticulous plan and a well-managed project as well. These activities go far beyond the normal activities in traditional lectures, enabling to outpace the difficulties that spur along the way that may be both complex and demotivating. This methodology has been implemented in the Integrated Master Degree on Industrial Engineering and Management (IEM), at one public university in Portugal, since the 2004/2005 academic year. The aim of this paper is to identify and discuss the main difficulties of the implementation of PBL, mainly from the teachers’ perspectives. Additionally, some effective strategies will be recommended to overcome such difficulties.